Livestock extension officers integrate herd management packages in their businesses in central Mali - Sow, Ahmadou; Sissoko, Oumou; Dao, M.; Rekik, Mourad; Hoek, Rein van der; Amole, Tunde A.; Idoudi, Zied; Rudiger, Udo; Tebourbi, Ons; Marshall, Karen; Dione, Michel M. (International Livestock Research Institute, 2025)
Small ruminant farmers in Mali face persistent challenges in health, nutrition, and reproduction management. To address these issues, public and private livestock health and management practitioners delivered an integrated herd management package to small ruminant producers using a behavior change communication approach. These trainings were carried out by 40 private livestock service providers, referred to here as livestock champions (LCs). In 2025, 1,442 (56%) men and 1,135 (44%) women small ruminants producers benefited from these trainings in 87 villages across 13 municipalities in central Mali.